Effect of Piezoelectric Sutural Ostectomies on Accelerated Bone-Borne Sutural Expansion - Alyessary, A.S.; Yap, A.U.J.; Othman, Siti Adibah; Rahman, Mohammad Tariqur; Radzi, Zamri (Elsevier, 2018)
Purpose The present study investigated the effect of piezoelectric sutural ostectomies on accelerated bone-borne sutural expansion.